2021
DOI: 10.1038/s41421-021-00302-0
|View full text |Cite
|
Sign up to set email alerts
|

Potent prophylactic and therapeutic efficacy of recombinant human ACE2-Fc against SARS-CoV-2 infection in vivo

Abstract: The current COVID-19 pandemic, caused by SARS-CoV-2, poses a serious public health threat. Effective therapeutic and prophylactic treatments are urgently needed. Angiotensin-converting enzyme 2 (ACE2) is a functional receptor for SARS-CoV-2, which binds to the receptor binding domain (RBD) of SARS-CoV-2 spike protein. Here, we developed recombinant human ACE2-Fc fusion protein (hACE2-Fc) and a hACE2-Fc mutant with reduced catalytic activity. hACE2-Fc and the hACE2-Fc mutant both efficiently blocked entry of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 73 publications
(102 reference statements)
2
82
0
Order By: Relevance
“…This long-lasting effect was also confirmed by other scientists [3]. Further, ACE2 decoy receptor was confirmed neutralization against authentic virus [4][5][6][7][8][9] and showed promising prophylactic and therapeutic efficacy in animal models [8].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…This long-lasting effect was also confirmed by other scientists [3]. Further, ACE2 decoy receptor was confirmed neutralization against authentic virus [4][5][6][7][8][9] and showed promising prophylactic and therapeutic efficacy in animal models [8].…”
Section: Introductionsupporting
confidence: 67%
“…As the receptor of SARS-CoV-2, ACE2 is promising to play these roles. ACE2 decoy receptor therapies have shown broad neutralization activity against existing variants (Table 1) and demonstrated promising ability by mutated RBD binding [10] or escape assay in co-incubation of ACE2 decoy receptor [8,9] to neutralize potential variants. Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…It can not only block the entry of SARS-CoV-2, SARS-CoV, and HCoV-NL63 into host cells, but also neutralize various variants of SARS-CoV-2, including the D614G and V367F mutants, B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.1 (Kappa), and B.1.617.2 (Delta). Most importantly, hACE2-Fc has a longer half-life in vivo than soluble ACE2 [68]. Another study demonstrated that an improved soluble ACE2, termed a "microbody", in which the ACE2 ectodomain was fused with Fc domain 3 of the immunoglobulin heavy chain, effectively inhibited the entry of SARS-CoV-2 pseudovirus and live SARS-CoV-2 in vitro and in a mouse model [69].…”
Section: Prolonging the Half-life Of Sace2 By Fusion With A Varied Fc Fragmentmentioning
confidence: 99%
“…In the study of SARS-CoV-2 infection, verified animal models are needed to fully reproduce the pathogenesis of the disease. Currently, promising animal infection models of SARS-CoV-2 have been reported, including a transgenic mouse model expressing human ACE2, Syrian hamster model, ferret model, cat model, and non-human primate model [68,[94][95][96]. The development of these animal models is crucial for vaccine evaluation and drug screening.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The virus reduces the expression of membrane-bound ACE2 (mACE2) by internalization and shedding, resulting in the relative dominance of AT1 receptor (AT1R)/aldosterone receptor (AldR) deleterious effects over the Mas receptor (MasR)/MrgD alamandin receptor (MrgD)/angiotenin II type 2 receptor (AT2R) protective cardiovascular and anti-inflammatory actions. ACE inhibitors (ACEI), angiotensin II type 1 receptor blockers (ARB), aldosterone receptor (AldR) blockers(Wilcox and Pitt, 2020), AT2R agonists(Tornling et al, 2021), recombinant human ACE2(Zhang et al, 2021), or kinin-kallikrein system inhibitors(Mansour et al, 2021) induce interactions with RAAS, which may render protection. Created with BioRender.com.…”
mentioning
confidence: 99%